Characteristics and co-admissions of mothers and babies admitted to residential parenting services in the year following birth in NSW: a linked population data study (2000-2012) - Hannah Grace Dahlen; Virginia Schmied; Cathrine Fowler; Lilian L. Peters; Simone Ormsby; Charlene Thornton (BMC, 2022)
Abstract Background There is a tiered healthcare system in Australia to support maternal and child health, including, non-psychiatric day stay and residential parenting services (RPS) such as Tresillian and Karitane (in New South Wales [NSW]). RPS are unique to Australia, and currently there is limited information regarding the healthcare trajectory of women accessing RPS and if they are more likely to have admissions to other health facilities within the first-year post-birth. This study aimed to examine differences in hospital co-admissions for women and babies admitted to RPS in NSW in the year following birth compared to non-RPS admitted women. Methods A linked population data study of all women giving birth in NSW 2000-2012. Statistical differences were calculated using chi-square and student t-tests. Results Over the 12-year timeframe, 32,071 women and 33,035 babies were admitted to RPS, with 5191 of these women also having one or more hospital admissions (7607 admissions). The comparator group comprised of 99,242 women not admitted to RPS but having hospital admissions over the same timeframe (136,771 admissions). Statistically significant differences between cohorts were observed for the following parameters (p ≤ .001). Based upon calculated percentages, women who were admitted to RPS were more often older, Australian born, socially advantaged, private patients, and having their first baby. RPS admitted women also had more multiple births and labour and birth interventions (induction, instrumental birth, caesarean section, epidural, episiotomy). Their infants were also more often male and admitted to Special Care Nursery/Neonatal Intensive Care. Additionally, RPS admitted women had more admissions for mental health and behavioural disorders, which appeared to increase over time. There was no statistical difference between cohorts regarding the number of women admitted to a psychiatric facility; however, women attending RPS were more likely to have mood affective, or behavioural and personality disorder diagnoses. Conclusion Women accessing RPS in the year post-birth were more socially advantaged, had higher birth intervention and more co-admissions and treatment for mental health disorders than those not accessing RPS. More research is needed into the impact of birth intervention and mental health issues on subsequent parenting difficulties.